Оптимальне керування інтенсивністю занурених точкових джерел води у ненасиченому пористому середовищі - Ляшко, С.І.; Клюшин, Д.А.; Тимошенко, А.А. (Доповіді НАН України, 2019)
Розглядається двовимірна квазілінійна задача точкового оптимального керування зволоженням прямокутної ненасиченої області пористого середовища з нульовими початковими умовами, нульовою вологістю
на границі та заданою досяжною цільовою вологістю. Запропоновано підхід, який використовує перетворення Кірхгофа, що дозволяє звести квазілінійну параболічну початково-крайову задачу до лінійної та безрозмірної. Показано коректність лінеаризованої безрозмірної задачі нестаціонарного вологоперенесення,
зокрема теореми щодо існування та єдиності узагальненого розв'язку, а також існування та єдиність оптимального керування потужністю занурених точкових джерел.
Наведено результати обчислювальних експериментів, які продемонстрували високу точність методу.
Запропонований метод дозволяє розв'язати актуальну задачу оптимального вибору параметрів системи
крапельного зрошення та збільшити її ефективність. The humidity transfer process through an unsaturated porous medium with inserted point sources modeled by
the Richards—Klute equation has calculation complexity and is unstable. The reason for that is a large number of
diverse parameters for the equation used to describe the physical process. To reduce the difficulty, an approach is
offered based on the Kirchhoff transformation, which allows one to bring down the quasilinear parabolic initialboundary
problem to a linear dimensionless one. A two-dimensional quasilinear problem of optimal control using
point sources for a rectangular unsaturated porous medium with zero initial conditions, zero humidity at the
bounds, and the achievable given target humidity is considered, studied, and solved for the first time.
The initial problem is transformed into the linear dimensionless optimal control problem of non-stationary
moisture transport in an unsaturated porous medium using the Kirchhoff transformation. A variation algorithm
identifying the optimal source power is used, which allows modeling the process with realistic assumptions. For
this algorithm, the finite difference method is used for both direct and conjugate problems, followed by the numerical
method application to solve the SLAE. The correctness of the linearized dimensionless problem of moisture
transport is shown. In particular, the theorems of existence and uniqueness of the generalized solution are
mentioned, as well as the existence and uniqueness of the optimal control over the source power.
The current paper is devoted to the modeling of the moisture transport from an inserted source in a dry
ground area. Results of numerical experiments demonstrating a high accuracy of the method are given. The proposed
method allows one to solve actual problems of optimal parameter choice for a drop irrigation system, and
to improve its effectiveness. Рассматривается двумерная квазилинейная задача точечного оптимального управления увлажнением прямоугольной ненасыщенной области пористой среды с нулевыми начальными условиями, нулевой влажностью на границе и заданной достижимой целевой влажностью. Предложен подход, использующий преобразование Кирхгофа, позволяющее свести квазилинейную параболическую начально-краевую задачу к
линейной и безразмерной. Показана корректность линеаризованной безразмерной задачи нестационарного
влагопереноса, в частности теоремы о существовании и единственности ее обобщенного решения, а также существовании и единственности оптимального управления мощностью заглубленных точечных источников.
Приведены результаты вычислительных экспериментов, которые продемонстрировали высокую
точность метода. Предложенный метод позволяет решить актуальную задачу оптимального выбора параметров систем капельного орошения и повысить ее эффективность.